(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Introduction: Wushu Sanda is a Chinese combat sport. Objective: To measure the time-motion structure of elite female wushu sanda athletes during the 13th World Wushu Championships in different weight divisions (light, middle, and heavy categories) and competition phases (eliminatory, quarterfinals, semifinals and finals). Material and methods: Fifty-five female athletes from 31 countries participated in 46 matches during the competition. All 46 matches, accounting 95 rounds, 35 in light, 25 in middle and 35 in heavyweight divisions, took part in the study. Matches were analyzed using the software Kinovea™. Each match was reproduced in slow motion (50%) twice; therefore, one athlete was observed each time to ensure that all activities would be registered, totalizing 92 observations (46 matches, 2 observations per match). We registered the time in observation, preparation, interaction, effort, pause, high-intensity and low-intensity activities. Results: Descriptive data showed an effort:pause ratio of 2.2:1, a high:low intensity efforts ratio of 1:1.3, and mean observation-preparation-interaction times of 4.5-1.2-4.2 seconds. When comparing by weight category, heavyweight categories had higher total fighting time per round than the light and middle categories. Also, heavyweight categories had longer preparation and interaction mean-time; and referee interruption time frequency, total and mean times than the light and middle categories. Total pause time was also higher for heavyweights. According to the competitive phase, semifinal matches had shorter observation times than eliminatory and final matches. Also, semifinal matches had lower low-intensity time than quarterfinals and finals. Conclusions: Wushu sanda is an intermittent combat sport, and female athletes present some time-motion differences according to weight division and competitive phase.